Validation of a mobile application for adults with neurological lower urinary tract dysfunction - Danielle Soraya Lourenço Fernandes Gomes; Priscilla Alfradique de Souza; Gisela Maria Assis; Danielle Galdino de Paula (Universidade de São Paulo, 2024)
Abstract Objective: to validate with experts the content of a mobile application to guide patients with neurological dysfunction of the lower urinary tract. Method: methodological study. For content validation, 81 specialist nurses took part. The data collection instrument was designed in the form of an electronic form, and included assessments of the application's objectives, content, language, relevance, functionality and usability. The data was submitted to descriptive and inferential statistical analysis, based on the measurement of the Content Validity Index. Results: the overall content validity index of the prototype application was 0.98. The lowest item (0.93) was related to the adequacy of the font size, and the highest module (1) was associated with usability, showing ease in handling the application. The experts recommended correcting spelling and grammar, as well as adding and minimizing information, standardizing language, among others. Conclusion: the content of the MeduLar sem Medo ® mobile app was validated with excellence by specialists, and presented important resources for teaching urinary dysfunction control and adherence to rehabilitation. With these results, it is possible to envision the next stages of validation, with application in the populations for which it is intended and incorporation of this care technology into the Unified Health System.